2018
DOI: 10.1167/iovs.18-24292
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Regulates Eyelid and Meibomian Gland Morphogenesis

Abstract: PurposeThe Meibomian gland (MG) produces the lipid layer of the tear film, and changes to the MG that lead to a decrease or alteration in lipid quality/content may lead to MG dysfunction, a major cause of evaporative dry eye disease with prevalence ranging from 39% to 50%. Little is known about the developmental cues that regulate MG morphogenesis and homeostasis. Our study investigates the role of hyaluronan (HA), a major extracellular matrix component, in eyelid formation and MG development and function.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…However, Has2 null mice are embryonic lethal; therefore, conditional knock-out mice were generated to remove Has2 from the corneal and limbal epithelium. For this task, transgenic mouse lines K14-rtTA (stock number 008099) and tetO-cre ( TC ) (stock number 006224) were obtained from The Jackson Laboratory and bred with Has2 floxed mice ( HAS2 flox/flox )30 to generate compound K14-rtTA, tetO-cre, and HAS2 flox/flox transgenic mice as previously shown 25,27,31. Administration of doxycycline chow was used to induce K14-driven persistent and irreversible excision of Has2 in tetratransgenic mice ( K14-rtTA; TC; HAS2 flox/flox ) generating HAS2 Δ/ΔCorEpi .…”
Section: Methodsmentioning
confidence: 99%
“…However, Has2 null mice are embryonic lethal; therefore, conditional knock-out mice were generated to remove Has2 from the corneal and limbal epithelium. For this task, transgenic mouse lines K14-rtTA (stock number 008099) and tetO-cre ( TC ) (stock number 006224) were obtained from The Jackson Laboratory and bred with Has2 floxed mice ( HAS2 flox/flox )30 to generate compound K14-rtTA, tetO-cre, and HAS2 flox/flox transgenic mice as previously shown 25,27,31. Administration of doxycycline chow was used to induce K14-driven persistent and irreversible excision of Has2 in tetratransgenic mice ( K14-rtTA; TC; HAS2 flox/flox ) generating HAS2 Δ/ΔCorEpi .…”
Section: Methodsmentioning
confidence: 99%
“…Hyaluronan (HA) is a linear polysaccharide formed of a repeating disaccharide unit composed of glucuronic acid and N-acetylglucosamine, and is one of the major components in tissues. Our recently published work identified an HA-rich extracellular matrix (ECM) surrounding the basal layer of Meibomian glands [121]. HA is synthesized by HA synthases (HASs), of which mammals have three isoforms: HAS1, HAS2 and HAS3 [121,122].…”
Section: Role Of Hyaluronan In Meibomian Gland Development and Homeosmentioning
confidence: 99%
“…Despite the countless studies dedicated toward establishing the therapeutic benefits of using HA and lubricin for treating ocular conditions, such as dry eye, and also the fact that eye drops containing HA are widely sold around the world, limited studies have investigated the long-term effects of continuous exposure of the ocular surface to HA and lubricin. We have recently shown that alterations in HA expression in keratin 14 positive cells leads to Meibomian gland and conjunctival hyperplasia ( Sun et al, 2018 ). Also, increased expression of HA throughout the cornea leads to lymphangiogenesis ( Sun et al, 2019 ).…”
Section: Involvement Of Proteoglycans and Glycosaminoglycans In Cornementioning
confidence: 99%
“…This work supports the need for more research focused on understanding the long-term effects of the topical administration of GAGs/PGs to the ocular surface. Some interesting studies have suggested that changes in HS and HA expression can lead to changes within lacrimal glands and Meibomian glands, and the expression of HS glycosyltransferases, such as HS2ST, HS3ST, and EXTL2, have been shown to be significantly downregulated in dry eye ( Pan et al, 2008 ; Mantelli et al, 2009 ; Qu et al, 2011 ; Patel et al, 2017 ; Sun et al, 2018 ).…”
Section: Involvement Of Proteoglycans and Glycosaminoglycans In Cornementioning
confidence: 99%